D–π–A Dyes that Contain New Hydantoin Anchoring Groups for Dye‐Sensitized Solar Cells. Issue 2 (25th January 2018) - Masui, Hisashi; Maitani, Masato M.; Fuse, Shinichiro; Yamamura, Ayaka; Ogomi, Yuhei; Hayase, Shuzi; Kaiho, Tatsuo; Tanaka, Hiroshi; Wada, Yuji; Takahashi, Takashi
Abstract: The development of new anchoring groups is important to facilitate effective co‐sensitization in dye‐sensitized solar cells (DSSCs). Herein, stable organic D–π–A dyes that contain new heterocyclic hydantoin‐based anchoring groups have been designed, synthesized, and used in DSSCs. These dye sensitizers were evaluated in terms of their absorption spectra, electrochemical properties, and performance in DSSC devices. Although only one‐third of the amount of hydantoin‐containing dyes adsorbed onto TiO2 relative to their cyanoacrylic‐acid‐containing analogues, they exhibited effective photoexcited electron‐transfer properties. External quantum efficiencies of over 80 % was observed, which were comparable to those of the cyanoacrylic‐acid‐containing dyes. In addition, the new hydantoin‐containing dyes exhibited significant robustness, which could allow improved stability of their corresponding photovoltaic devices under harsh conditions, such as high temperature and humidity. Abstract : Too young to dye : D–π–A dyes with new anchoring groups have been designed, synthesized, and used in dye‐sensitized solar cells (DSSCs). The dyes were evaluated in terms of their absorption spectra, electrochemical properties, and device performance. Hydantoin‐containing dyes displayed effective photoexcited electron‐transfer properties.